Deforestation patterns shape population structure of the Magellanic Woodpecker (Campephilus magellanicus) in southern Chile - Yanina Poblete (Resilience Alliance, 2020)
One important landscape-scale consequence of deforestation is reduced connectivity, which has the potential to isolate populations in ways that affect genetic diversity and population structure. Among the many regions of the world where this scenario has played out is the South American temperate forest (SATF) in southern Chile, and there is now strong concern about the population viability of forest taxa. We studied one such species, the Magellanic Woodpecker (Campephilus magellanicus), a forest specialist that is now listed as vulnerable in parts of its range in Chile. We characterized genetic variability and population structure from 33 samples of Magellanic Woodpeckers from two large but isolated populations in Nahuelbuta National Park in the Coastal mountain range and the Conguillío National Park in the Andes using ddRAD-seq method. We found lower genetic variability in Nahuelbuta than Conguillío, but inbreeding values (FIS) did not show evidence for inbreeding depression. Results suggest the presence of two genetic clusters, with an average FST value of 0.04. Phylogenetic analysis showed that the Nahuelbuta population forms a clade that is nested within the individuals from Conguillío, suggesting limited gene flow between these populations. Our results support the idea that extensive deforestation has played a role in shaping the genetic patterns that we have identified. Because of this, we emphasize the need for regional planning to increase the structural connectivity between fragments of mature native forests, to provide an opportunity for the persistence of Magellanic Woodpeckers in this region.